Theatres of Agitation - Andrew Westerside (2018)
Theatres of Agitation: Performing Politics on the 21st Century Stage (2015-2018)This three-year research project was a collaboration between Dr Andrew Westerside (University of Lincoln, Principal Investigator) and Proto-type Theater (Co-I, partner)The project took as its starting point a critical (practice-led) study into the development of practical methodologies for staging affective radical and resistance politics on contemporary British Stages.Research Imperatives/Questions:1.Is it possible to determine, through studio-led research processes, practical and replicable methodologies for staging radical or agitational political discourse on contemporary British stages?2.How might those methodologies be used to create touring performance works such that their efficacy can be tested against the sector?Research Outputs1.Performance: A Machine They’re Secretly Building (2016) (writer, director: Andrew Westerside) (Eprint ID: 23365)2.Performance: The Audit (or Iceland, a modern myth) (2018) (writer, director: Andrew Westerside) (Eprint ID: 34250)3.Publication: Westerside, A. & Proto-type Theater (2017) A Machine they’re Secretly Building. London and New York: Oberon (Eprint ID: 29435)4.Publication: Westerside, A. & Proto-type Theatre (2018) The Audit (or Iceland, a modern myth). London and New York: Oberon (Eprint ID: 34251)Measures of Success•Funding and Commissions:o£116,563 Arts Council England (RQ1)o~£20,000 Venue Commissions and Investment (RQ1)•Performances at over 20 major UK venues (including):oSummerhall, Edinburgh, Southbank Centre, London, Oxford Playhouse, MAC, Birmingham, and The Lowry, Manchester (RQ1)•Reviews and Awards:oAMTSB long-listed for the 2017 Amnesty International Freedom of Expression Award (RQ2)oAMTSB selected for 2017 British Council Showcase (RQ2)oMultiple 4*+ reviews (including 4* from the Guardian) (RQ2)•The development of successful and replicable practical methodologies resulted in an invitation to contribute to Woods, N (2018) Making Postdramatic Theatre: A ...